Pricing and Producer-Retailer Supply Chain Coordination: A Game Theory Approach - Utama, KF. Sunny Cahya; Lukitosari, Valeriana (Journal of Applied Informatics and Computing, 2024)
Supply chain process is interdependent. Starting from procurement of raw materials, production, distribution, and finally the goods reaching consumers will influence each other. The costs of goods and services will be somewhat impacted by these social habits. Producers and merchants must comprehend these social behaviors in order to properly establish prices and the distribution of goods. This includes determining the prices of goods and services. Offering manufacturers who participate in cooperative advertising schemes money for a percentage of the costs connected with local advertising encourages retailers to launch additional promotional activities. The aim of this research is to investigate how cooperative pricing and advertising can improve supply chain coordination using consumer demand functions. A model based on game theory that takes the dynamics of power in the supply. A series of numerical simulations is presented to illustrate the optimal solution of channel members based on scenarios that illustrate, understand and compare the fundamental results of the game models. The results of this research are that retail price decisions are influenced by the level of competition and product differentiation. The results show that retail margins depend on local ( ) and national ( ) advertising effectiveness values. In addition, retailers can gain greater profits by setting higher prices in conditions of low price elasticity but must consider consumer sensitivity to price to maximize profits.